Education of Cardiac Resuscitation through Audiovisual Media on Basic Life Assistance Knowledge in Patients with A History of Cardiovascular System Disorders - Satriani, Satriani; Thalib, Abdul Herman Syah (Genius Journal, 2026)
Introduction: Cardiovascular disease is the main cause of global mortality in the world, especially in cases of heart failure. Heart failure is a condition when the heart suddenly stops working, whether in people who are already known to have heart disease or in people who have not yet been diagnosed. Objective: Knowing the level of basic life support knowledge before and after being given the implementation of cardiopulmonary resuscitation education using audiovisual media. Method: The design applied in this writing is a case study, in carrying out a descriptive exploration of the main idea of the discussion, namely the Implementation of Cardiopulmonary Resuscitation (CPR) Education with Audiovisual Media on Basic Life Support Knowledge in Patients with a History of Cardiovascular System Disorders. Result: Before implementing Cardiopulmonary Resuscitation (CPR) Education with Audiovisual Media on Basic Life Support in Patients with a History of Cardiovascular System Disorders for 3 days, the level of knowledge of the respondent, Mrs. R 25% (less) and Mrs. E 35% (less) and after implementing Cardiopulmonary Resuscitation (CPR) Education with Audiovisual Media on Basic Life Support in Patients with a History of Cardiovascular System Disorders for 3 days, the respondent's level of knowledge increased, Mrs. R increased 75% (enough) and Mrs. E increased 75% (enough). Conclusion: Implementation of Cardiopulmonary Resuscitation (CPR) Education with Audiovisual Media on Basic Life Support for Patients with a History of Cardiovascular System Disorders can increase a person's knowledge.